2005
DOI: 10.1186/1477-7525-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: The development and validation study of the Clinical Chronic Obstructive Disease (COPD) Questionnaire (CCQ) has recently been published in this journal. The CCQ is the first questionnaire that incorporates both clinician and patient guideline goals in the clinical control evaluation of patients with COPD in general clinical practice. The aim of this study is the validation of the CCQ questionnaire in Italian, in specific pulmonary disease clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 12 publications
5
24
1
3
Order By: Relevance
“…Patients with more severe stages of COPD reported worse health status, measured with both CAT and CCQ similarly to other studies [21,22]. This is true for both severity scales GOLD and BODE used in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Patients with more severe stages of COPD reported worse health status, measured with both CAT and CCQ similarly to other studies [21,22]. This is true for both severity scales GOLD and BODE used in this study.…”
Section: Discussionsupporting
confidence: 81%
“…The original research indicated the CCQ was a reliable, valid tool for measuring health-related quality of life in patients with COPD 27. The CCQ was translated into more than 60 languages worldwide and also was validated to show it had good psychometric properties 28,29…”
Section: Methodsmentioning
confidence: 99%
“…We expected that there would be a weak correlation between FEV 1 and a patient’s health related quality of life score, while the correlation between EQ-5D index and CCQ score was moderate to high based on previous publications [8,9,12]. The internal consistency of the CCQ was evaluated with Cronbach’s alpha.…”
Section: Methodsmentioning
confidence: 99%